Low-temperature selective oxidation of methane over distant binuclear cationic centers in zeolites - Tabor, Edyta; Lemishka, Mariia; Sobalik, Zdenek; Mlekodaj, Kinga; Andrikopoulos, Prokopis C.; Dedecek, Jiri; Sklenak, Stepan (Nature Publishing Group, 2019)
Highly active oxygen capable to selectively oxidize methane to methanol at low temperature can be prepared in transition-metal cation exchanged zeolites. Here we show that the alpha-oxygen stabilized by the negative charges of two framework aluminum atoms can be prepared by the dissociation of nitrous oxide over distant binuclear cation structures (M(II) ... M (II), M = cobalt, nickel, and iron) accommodated in two adjacent 6-rings forming cationic sites in the ferrierite zeolite. This alpha-oxygen species is analogous to that known only for iron exchanged zeolites. In contrast to divalent iron cations, only binuclear divalent cobalt cationic structures and not isolated divalent cobalt cations are active. Created methoxy moieties are easily protonated to yield methanol, formaldehyde, and formic acid which are desorbed to the gas phase without the aid of water vapor while previous studies showed that highly stable methoxy groups were formed on isolated iron cations in iron exchanged ZSM-5 zeolites.
Nízkoteplotní selektivní oxidace metanu na vzdálených binukleárních kationtových centrech zeolitů
Keywords: initio molecular-dynamics; total-energy calculations; o-t vibrations; n2o decomposition; computer experiments; classical fluids; periodic dft; alpha-sites; fe-bea; benzene; molekulární dynamika; DFT; zeolit; selektivní oxidace; přechodné kovy